A comparative evaluation of microleakage and dentin shear bond strength of three restorative materials. Issue 1 (31st December 2022) - Kumari, Alpana; Singh, Namita
Abstract: Aim: To evaluate the microleakage and dentin shear bond strength of two glass containing restorative materials, Zirconomer and Cention N, and to compare them with a conventional glass ionomer cement (GIC) (GC Fuji II). Materials and methods: Zirconomer (Shofu) and GC Fuji II (GC Corp.) are self-curing GICs whereas Cention N (IvoclarVivadent) also offers a self-curing option as well as the option of light-curing using an adhesive. For evaluating microleakage, standardized class V cavities were prepared on the buccal surface of 30 premolars. The cavities were restored with one of the three restorative materials ( n = 10) according to manufacturers' instructions, Cention N being used with an adhesive (Te-EconomBond, IvoclarVivadent) and in the light-curing mode. After restoration and thermocycling, the microleakage assessment was made under a stereomicroscope at 40x magnification following immersing of the teeth in 0.5% methylene blue dye and buccolingual sectioning. For evaluating dentin shear bond strength, the occlusal surface of the 30 premolars was ground flat, and cylinders of the three restorative materials ( n = 10) were bonded to the occlusal surface according to manufacturers' instructions, Cention N being used with an adhesive (Te-EconomBond, IvoclarVivadent) and in the light-curing mode. Following 24-h storage at 100% humidity, the dentin shear bond strength was measured and the fracture mode was determined under a stereomicroscope at 10× magnification. Data were statistically analyzed using Mann–Whitney and Scheffé tests ( p = .05). Results: Cention N displayed significantly less microleakage than did Zirconomer and GC Fuji II at occlusal as well as the gingival margins. Dentin shear bond strength varied significantly between 5.15 and 9.89 MPa with Cention N showing the highest bond strength and GC Fuji II the lowest. Conclusion: In this in vitro evaluation, Cention N consistently performed better than the conventional GIC (GC Fuji II) as well as Zirconomer.